Isolation and characterization of a Chlamydia muridarum tc0237 mutant from a genetic screen that is attenuated in epithelial cells. - Kaylee R Jacobs; Caleb M Ardizzone; Arkaprabha Banerjee; Evelyn Toh; Xiaoli Zhang; David E Nelson (PLoS ONE)
Chlamydia are obligate intracellular bacterial pathogens that infect a wide range of vertebrate hosts. Despite having highly conserved genomes, closely related Chlamydia species can exhibit distinct host and tissue tropisms. The host tropisms of the human pathogen Chlamydia trachomatis and the closely related mouse pathogen Chlamydia muridarum are influenced by their ability to evade host immune responses, particularly those mediated by interferon gamma. However, there is evidence that tissue tropism is driven by additional poorly understood host and Chlamydia factors. In this study, we used a forward genetic approach to investigate the mechanisms that mediate C. muridarum tissue tropism. We conducted a tropism screen using a randomly mutagenized C. muridarum library and murine cell lines representing different tissues. We identified a mutant isolate whose growth was restricted in murine rectal and oviduct epithelial cells in an interferon gamma-independent manner. This phenotype was mapped to a missense mutation in tc0237, a gene that mediates the affinity of C. muridarum for cultured human epithelial cells. Our analysis of growth dynamics showed that the tc0237 mutant exhibits a developmental delay in rectal epithelial cells. Together, these results suggest that TC0237 plays a role in C. muridarum tissue tropism.